Ceria nanoparticles enhance endochondral ossification–based critical‐sized bone defect regeneration by promoting the hypertrophic differentiation of BMSCs via DHX15 activation. Issue 5 (18th February 2019) - Li, Jianmei; Kang, Fei; Gong, Xiaoshan; Bai, Yun; Dai, Jingjin; Zhao, Chunrong; Dou, Ce; Cao, Zhen; Liang, Mengmeng; Dong, Rui; Jiang, Hong; Yang, Xiaochao; et al.
ABSTRACT: Central ischemic necrosis is one of the biggest obstacles in the clinical application of traditional tissue‐engineered bone (TEB) in critical‐sized bone defect regeneration. Because of its ability to promote vascular invasion, endochondral ossification‐based TEB has been applied for bone defect regeneration. However, inadequate chondrocyte hypertrophy can hinder vascular invasion and matrix mineralization during endochondral ossification. In light of recent studies suggesting that ceria nanoparticles (CNPs) improve the blood vessel distribution within TEB, we modified TEB scaffold surfaces with CNPs and investigated the effect and mechanism of CNPs on endochondral ossification–based bone regeneration. The CNPs used in this study were synthesized by the microemulsion method and modified with alendronate‐anchored polyethylene glycol 600. We showed that CNPs accelerated new bone formation and enhanced endochondral ossification–based bone regeneration in both a subcutaneous ectopic osteogenesis model and a mouse model of critical‐sized bone defects. Mechanistically, CNPs significantly promoted endochondral ossification–based bone regeneration by ensuring sufficient hypertrophic differentiation via the activation of the RNA helicase, DEAH (Asp‐Glu‐Ala‐His) box helicase 15, and its downstream target, p38 MAPK. These results suggested that CNPs could be applied as a biomaterial to improve the efficacy of endochondral ossification–based bone regeneration in critical‐sized bone defects.—Li, J., Kang, F., Gong, X., Bai, Y., Dai, J., Zhao, C., Dou, C., Cao, Z., Liang, M., Dong, R., Jiang, H., Yang, X., Dong, S. Ceria nanoparticles enhance endochondral ossification‐based critical‐sized bone defect regeneration by promoting the hypertrophic differentiation of BMSCs via DHX15 activation. FASEB J. 33, 6378–6389 (2019). www.fasebj.org